Implementation of the Balanced Scorecard Approach in Industries: A Systematic Literature Review - Dias Sukma Irawati (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2020)
A systematic review is a method used by researchers to identify, assess, and interpret all findings on research topics to be understood from various research perspectives before the researcher conducted the primary research. This article aims to determine which areas the Balanced Scorecard has used and applied using a systematic review method. The Balanced Scorecard is a concept for measuring the performance of an organization with four different perspectives. The preliminary article screening technique used is to review research papers with the keyword